Study the Efficiency Hypothesis in the Egyptian Stock Market - Abdelzaher, Mai Ahmed (International Journal of Economics and Financial Issues, 2021)
This article aims is to verify if the Egyptian stock market has information efficiency (market efficiency assumptions) by studying the presence of time series properties for daily stock returns between 2005 and 2015. Parametric and non-parametric tests are used to achieve this purpose, such as ADF/PP unit root- RUNS TEST- Perron - run test. The Jarque– Bera test was used to measure the moderation of returns; the GARCH model and ARCH model are used also. The results referring to the Egyptian stock market follow the inefficient form, and the prices are closer to random traffic standards, showing that the price changes are random. Thus, there may be shares presented at less than their real value. Additionally, the consequence of the inefficiency of the Egyptian stock market on the weak level, given that the prices of stock prices do not reflect all historical information, it is possible for market participants to achieve unusual returns by using historical prices of shares. Keywords: relevant information, risk market, rational investor JEL Classifications: G40,G14 DOI: https://doi.org/10.32479/ijefi.10634